Tecnologias fotovoltaicas e desenvolvimento de programa para o planejamento de sistemas de módulos solares - Miranda, Ana Luíza Giacon de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The increasing use of electric power by modern society has caused the growth of its production from the most varied sources. Even countries with large water resources, such as Brazil, make use of other more polluting sources to supply the demand in periods of drought. At the same time, renewable and less polluting energy sources that can make up the country energy matrix, such as electricity produced from photovoltaic cells, are increasingly available. To do so, it is necessary to reduce the costs of its production, as well as to facilitate projects for its dimensioning. The present work proposes a model that based on the local insolation and consumption of the considered population defines the number of solar modules needed to supply the demand and its approximate final cost. In order to enable the development of the Solar Energy model, a bibliographic research was carried out on the application of this technology in Brazil and on the solar modules available in the market. The database was created considering this information, presenting values of monthly insolation in each Brazilian State Capital and specifications of the solar technologies that are sold in the country. The Solar Energy model provides data to perform simulations of the implantation of photovoltaic systems both in cities and in residences as well. Through this strategic practice it is possible to verify the number of modules to be installed, required area, annual savings, reduction of carbon dioxide and the returning time of the investment. The aims are to discuss the advantages of solar energy, to analyze different scenarios of the application of photovoltaic systems, as illustrated in the case study, and to collaborate with the expansion of the use of solar energy for the production of electricity, a source that is less polluting and more sustainable. As an example, when using the model to simulate the installation of a photovoltaic...

A crescente utilização de energia elétrica pela sociedade moderna provocou o aumento de sua produção a partir das mais variadas fontes. Mesmo países com grandes recursos hídricos, como o Brasil, acabam fazendo uso de outras fontes mais poluentes para suprir a demanda em períodos de estiagem. Paralelamente, são cada vez mais disponíveis fontes renováveis e menos poluentes de energia que podem compor a matriz energética dos países, como a energia elétrica produzida a partir de células fotovoltaicas. Para tanto, há que se baratear os custos para sua produção, bem como facilitar projetos para o seu dimensionamento. O presente trabalho propõe um modelo que a partir da insolação local e consumo da população considerada define o número de módulos solares necessários para suprir a demanda e seu custo final aproximado. Para possibilitar o desenvolvimento do modelo Energia Solar, realizou-se pesquisa bibliográfica sobre a aplicação dessa tecnologia no Brasil e sobre os módulos solares disponíveis no mercado. O banco de dados foi criado a partir dessas informações, apresentando valores de insolação mensal das capitais brasileiras e especificações das tecnologias solares comercializadas atualmente no país. O modelo Energia Solar fornece dados para realizar simulações da implantação de sistemas fotovoltaicos tanto em cidades como em residências. Através dessa estratégica prática é possível verificar a quantidade de módulos a serem instalados, área necessária, economia anual, redução de dióxido de carbono e tempo de retorno do investimento. Com isso, discutiu-se as vantagens da energia solar, observando diferentes cenários da aplicação de sistemas fotovoltaicos, como ilustrado no estudo de caso, e colaborando com o incremento da utilização da energia solar para a produção de eletricidade, fonte menos poluidora e, portanto, mais sustentável...
Keywords: Energia solar; Sistemas de energia fotovoltaica; Geração de energia fotovoltaica; Celulas solares; Energia elétrica; Energia - Fontes alternativas; Sustentabilidade; Brasil